Enantiospecific Synthesis, Chiral Separation, and Biological Activity of Four Indazole-3-Carboxamide-Type Synthetic Cannabinoid Receptor Agonists and Their Detection in Seized Drug Samples - Antonides, Lysbeth H.; Cannaert, Annelies; Norman, Caitlyn; Vives, Loelia; Harrison, Aidan; Costello, Andrew; Nic Daeid, Niamh; Stove, Christophe P.; Sutcliffe, Oliver B.; McKenzie, Craig (Frontiers in Chemistry, 2019)
Synthetic cannabinoid receptor agonists (SCRAs) have been the largest group of illicit psychoactive substances reported to international monitoring and early warning systems for many years. Carboxamide-type SCRAs are amongst the most prevalent and potent. Enantiospecific synthesis and characterisation of four indazole-3-carboxamides, AMB-FUBINACA, AB-FUBINACA, 5F-MDMB-PINACA (5F-ADB) and AB-CHMINACA is reported. The interactions of the compounds with CB1 and CB2 receptors were investigated using a G-protein coupled receptor (GPCR) activation assay based on functional complementation of a split NanoLuc luciferase and EC50 and Emax, values determined. All compounds demonstrated higher potency at the CB2 receptor than at the CB1 receptor and (S)-enantiomers had an enhanced potency to both receptors over the (R)-enantiomers. The relative potency of the enantiomers to the CB2 receptor is affected by structural features, the difference being more pronounced for compounds with an amine moiety (AB-FUBINACA and AB-CHMINACA) than those with an ester moiety (AMB-FUBINACA and 5F-MDMB-PINACA). An HPLC method was developed to determine the prevalence of (R)-enantiomers in seized samples. Lux® Amylose-1 (Amylose tris(3,5-dimethylphenylcarbamate)) has the greatest selectivity for the SCRAs with a terminal methyl ester moiety and a Lux® i-Cellulose-5 column for SCRAs with a terminal amide moiety. Optimised isocratic separation methods yielded enantiomer resolution values (Rs) ≥ 1.99. Achiral GC-MS analysis of seized herbal materials (n=16), found 5F-MDMB-PINACA (<1.0-91.5 mg/g herbal material) and AMB-FUBINACA (15.5-58.5 mg/g herbal material) respectively. EMB-FUBINACA, AMB-CHMICA, 5F-ADB-PINACA isomer 2 and ADB-CHMINACA were also tentatively identified. Analysis using chiral chromatography coupled to photodiode array and quadrupole time of flight mass spectrometry (chiral HPLC-PDA-QToF-MS/MS) confirmed that the (S)-enantiomer predominated in all samples (93.6 to 99.3% (S)-enantiomer). Small but significant differences in synthesis precursor enantiopurity may provide significant differences between synthesis batches or suppliers and warrants further study. A method to compare potency between samples containing different SCRAs at varying concentrations was developed and applied in this small preliminary study. A ten-fold difference in the ‘intrinsic’ potency of samples in the study was noted. With the known heterogeneity of SCRA infused materials, the approach provides a simplified method for assessing and communicating the risk of their use.